Effect of Subantimicrobial Dose Doxycycline Treatment on Gingival Crevicular Fluid Levels of MMP-9 and MMP-13 in Periodontitis Stage 2, Grade B in Subjects with Type 2 Diabetes Mellitus - Mai S. Attia; Jazia A. Alblowi (Journal of Immunology Research)
The aim of this study was to investigate the effect of using subantimicrobial dose doxycycline as an adjunct in periodontitis stage 2, grade B in subjects with type 2 diabetes mellitus. A total of thirty patients were divided into the following two groups with reference to periodontitis, type 2 diabetes mellitus, and administration of the doxycycline drug: Group I: patients with periodontitis stage 2, grade B and type 2 diabetes mellitus who received SRP only. Group II: patients with periodontitis stage 2, grade B and type 2 diabetes mellitus who received SRP and doxycycline 20 mg. The following clinical measurements were recorded at baseline (prior to scaling and root planning) and after one and three months postoperatively: GI, PI, and PD with a periodontal calibrated probe. The levels of both MMP-9 and MMP-13, from 60 GCF samples, were analyzed by ELISA. Patients treated with SRP and doxycycline 20 mg showed a significant reduction of PD, PI, GI, MMP-9, and MMP-13 than patients who received SRP only. Improvements in parameters clinically and biochemically were observed following the adjunctive use of doxycycline subantimicrobial dose therapy for the management of stage 2, grade B periodontitis patients with type 2 diabetes mellitus.